2005
DOI: 10.1104/pp.104.055665
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Characterization of a Formin-Like Protein (AtFH8) from Arabidopsis

Abstract: The actin cytoskeleton is required for many cellular processes in plant cells. The nucleation process is the rate-limiting step for actin assembly. Formins belong to a new class of conserved actin nucleator, which includes at least 2 formin homology domains, FH1 and FH2, which direct the assembly of unbranched actin filaments. The function of plant formins is quite poorly understood. Here, we provide the first biochemical study of the function of conserved domains of a formin-like protein (AtFH8) from Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 59 publications
(81 reference statements)
4
109
2
2
Order By: Relevance
“…Actin-disrupting drugs inhibited or delocalized root hair growth (Bibikova et al, 1999;Ketelaar et al, 2003), consistent with reports showing that knockouts to the vegetative ACT2 gene in Arabidopsis have distorted root hair morphology (Ringli et al, 2002). Moreover, altering the expression of genes encoding proteins that affect actin turnover, such as profilin, actin-depolymering factor, formin, actininteracting protein, and cyclase-associated protein, disrupted normal root hair development (Ramachandran et al, 2000;Dong et al, 2001;Yi et al, 2005;Deeks et al, 2007;Ketelaar et al, 2007).…”
supporting
confidence: 62%
“…Actin-disrupting drugs inhibited or delocalized root hair growth (Bibikova et al, 1999;Ketelaar et al, 2003), consistent with reports showing that knockouts to the vegetative ACT2 gene in Arabidopsis have distorted root hair morphology (Ringli et al, 2002). Moreover, altering the expression of genes encoding proteins that affect actin turnover, such as profilin, actin-depolymering factor, formin, actininteracting protein, and cyclase-associated protein, disrupted normal root hair development (Ramachandran et al, 2000;Dong et al, 2001;Yi et al, 2005;Deeks et al, 2007;Ketelaar et al, 2007).…”
supporting
confidence: 62%
“…Root hair deformation results from cytoskeletal reorganization and cell wall deposition that redirects polar tip growth. Two genes up-regulated in the 3-to 6-h interval are homologs of Arabidopsis Formin-Like8 (AtFH8) and Abscisic Acid Insensitive-Like (ABIL), genes directly linked to actin nucleation and severing (Yi et al, 2005). ABIL functions in the SCAR/WAVE complex that regulates the actin cytoskeleton in tip-growing cells and during infection thread progression in legumes (Yokota et al, 2009;Miyahara et al, 2010;Hossain et al, 2012) and was recently observed to be up-regulated in root hairs undergoing infection (Breakspear et al, 2014).…”
Section: Early Induction Of Genes Involved In Polar Root Hair Growthmentioning
confidence: 99%
“…The over-expression of Arabidopsis formin AtFH8 was observed to cause an increase in the overall amount of filamentous actin within root hairs, as well as the precocious extension of actin bundles to the extreme tip [Yi et al, 2005]. In addition, the morphological effects on root hairs resemble those induced on pollen tubes by the over-expression of AtFH1 [Cheung and Wu, 2004], including swelling, defects in polarization and growth arrest.…”
Section: Forminsmentioning
confidence: 95%
“…fimbrins and LIM proteins. Indeed, nucleating, capping and/or severing activities have been attributed to members of the villin and formin families [Deeks et al, 2005;Ingouff et al, 2005;Michelot et al, 2005;Yi et al, 2005] but not yet to a plant fimbrin or LIM protein. Also, additional rigorous biochemical work is needed to assert that fimbrin and LIM proteins are specifically dedicated to the bundling of AFs.…”
Section: Generalitiesmentioning
confidence: 99%